Impact of Employee Selection on Work Productivity: (Case Studi At PT. Prima Alloy Steel Universal Gedangan Sidoarjo) - Achmad Daengs GS; Enny Susanti; Rina Dewi; Retno Susanti; Ramansyah Hidayat (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
Prima Allioy Steel Universal Gedangan is a company operating in the field of steel. Every year this PT carries out selection of new employees. To find out whether the addition of employees will reduce productivity, research is needed entitled